Association between health-related physical fitness, extracurricular physical activities and body adiposity in with a representative sample adolescents from Florianópolis, Brazil Asociación entre aptitud física relacionada con la salud, actividades físicas extraescolares y adiposidad corporal en una muestra representativa de adolescentes de Florianópolis, Brasil - Parmigiani De Marco J.C.* (2023)
© Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF).Objective: To identify associations between physical fitness, extracurricular physical activity, and body adiposity in a representative sample of adolescents from Florianópolis, Brazil. Methods: This cross-sectional, school-based study included 981 adolescents aged 14–18 years attending public schools in Florianópolis, Brazil. The dependent variable was body adiposity, calculated from the sum of triceps and subscapular skinfold thicknesses. Participation in extracurricular physical activity and health-related physical fitness components (flexibility, muscle strength and endurance, cardiorespiratory fitness) were independent variables. Results: The prevalence of high body adiposity was 27.1%, not differing between sexes (boys = 25,0%, girls = 29.4%). There was a negative association between body adiposity, cardiorespiratory fitness, and abdominal endurance in both sexes. The final model explained 58.2% of the variation in body adiposity scores in girls and 47.9% in boys. Negative associations of body adiposity with cardiorespiratory fitness (girls: β = -0.752, p < 0.001; boys: β = -0.655, p < 0.001) and abdominal endurance (girls: β = -0.070, p = 0.021; boys: β = -0.077, p = 0.021) were found in both sexes. Negative associations of body adiposity with extracurricular physical activity were observed in girls (β = -0.078, p = 0.010) and with grip strength (β = -0.121, p < 0.001) and flexibility (β = - 0.082, p = 0.015) in boys. Conclusion: Regardless of sex, adolescent groups with low cardiorespiratory fitness and abdominal endurance were the most affected by high body adiposity. Furthermore, lower participation in extracurricular physical activity in girls and lower strength and flexibility in boys were associated with higher body adiposity.